(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Treatment of persistent macular holes (MH) remains a challenge in spite of recent advances in macular surgery. In re-surgery in case of persistent MH, there is lack of internal limiting membrane (ILM) tissue for adequate MH closure. Application of leucocyte and platelet rich plasma (PRP) to the macular hole is one of the various techniques that may be used to improve the success rate of surgery for persistent MHs. The use of the funnel-shaped Ycellbio system with a red blood cell (RBC) control lever provides easy and effective PRP extraction process. Purpose: To assess the efficacy of surgical treatment for persistent MHs with application of the PRP obtained with YCELLBIO PRP preparation kit to the MH area. Material and Methods: Ten patients with eyes diagnosed with persistent MH were under observation at the Kyiv Municipal Clinical Eye Hospital “Eye Microsurgery Center” from September 2018 to February 2019. Before re-surgery, mean macular hole size was 894 ± 115 ?m, and best-corrected visual acuity varied from 0.03 to 0.1. PRP was obtained using a fixed-angle rotor centrifuge at 3600 rpm with an YCELLBIO PRP preparation kit. Each patient received a closed subtotal vitrectomy with application of the PRP to MH area and subsequent vitreous endotamponade with 20% С3F8. Results: The surgical procedure for persistent MH promoted anatomical closure in 9/10 eyes (9/10 patients). In addition, postoperative BCVA was 0.1 or better in 8/10 patients, and worse than 0.1 in 2/10 patients. Conclusion: Application of the PRP obtained with the Ycellbio system is an effective method of treatment and may be considered as a method of choice for surgical treatment of persistent macular holes.